2014
DOI: 10.3748/wjg.v20.i14.3719
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of hepatic metastases from colorectal cancer - pathobiological pathways with clinical significance

Abstract: Colorectal cancer hepatic metastases represent the final stage of a multi-step biological process. This process starts with a series of mutations in colonic epithelial cells, continues with their detachment from the large intestine, dissemination through the blood and/or lymphatic circulation, attachment to the hepatic sinusoids and interactions with the sinusoidal cells, such as sinusoidal endothelial cells, Kupffer cells, stellate cells and pit cells. The metastatic sequence terminates with colorectal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 184 publications
(207 reference statements)
1
52
0
4
Order By: Relevance
“…It was noted that TAMs play important role in tumor development and progression in liver [47]. TAMs are lured and activated by cancer cells, which secrete either M-CSF (macrophage colony stimulating factor) [47] or/and CEA (carcinoembryonic antigen) [52]. Our previous report showed that number of TAMs in LM was associated with overall survival (OS) [53].…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that TAMs play important role in tumor development and progression in liver [47]. TAMs are lured and activated by cancer cells, which secrete either M-CSF (macrophage colony stimulating factor) [47] or/and CEA (carcinoembryonic antigen) [52]. Our previous report showed that number of TAMs in LM was associated with overall survival (OS) [53].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data presented the modulatory role of hepatic microenvironment both in initiation and progression of the primary carcinogenic process as well as in establishment of optimal conditions for metastatic colonization and development [5,12,21,26]. A necessary condition for HCC initiation and development seems to be the presence of activated inflammatory cells in the liver, through their action on signaling pathways, which results in enhanced cellular turnover and acquisition of critical modifications for the malignant transformation [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported in HM that highly aggressive Dukes C and D malignant cells of CRC-origin can trigger apoptotic death of TAMs and monocytes by the secretion of high mobility group box 1 (HMGB1) protein [38]. On the other hand, malignant cells can attract TAMs by secretion of carcinoembryonic antigen (CEA) followed by the release of growth factors by enticed macrophages [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For one, the liver is connected via the blood circulation to those sites where many malignant tumours arise [18]. In addition, the healthy liver actually displays intrinsic architectural and functional features, whose balance can easily be tipped towards favouring metastasis to this organ [9,19,20], even without priming by factors secreted by the original tumour site, as it would be the case in classic premetastatic niche formation. They comprise the following: (1) the liver-specific microcirculation with its unique sinusoidal cell population, (2) the perivascular mesenchymal cells including hepatic stellate cells (HSCs), (3) the morphologically and metabolically heterogeneous parenchymal cell compartment, and (4) the hepatic regional immunity (Fig.…”
Section: Intrinsic Metastasis-supporting Features Of the Livermentioning
confidence: 99%